ENHANCING STATISTICAL LEARNING MOTIVATION THROUGH LECTURER COMPETENCY: A STUDY AT UNIVERSITAS MURNI TEGUH, INDONESIA - Simarmata, Hengki Mangiring Parulian; Saragih, Doris Yolanda; Sirait, Erwin; Lie, Darwin (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to examine the influence of statistics lecturer competence and teaching strategies on students’ interest in learning statistics at Universitas Murni Teguh PSDKU Pematangsiantar. Using a quantitative approach with a sample of 105 undergraduate students, data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that lecturer competence has a strong and significant positive effect on students’ interest (β = 0.684; p < 0.001), indicating that pedagogical skills, subject mastery, and communicative ability play a crucial role in motivating students to engage with statistical content. Conversely, teaching strategies showed a significant yet negative effect (β = -0.188; p < 0.05), suggesting a potential mismatch between current instructional approaches and students’ learning preferences. Validity and reliability tests confirmed that all constructs met convergent validity (outer loading > 0.70), internal consistency (Cronbach’s alpha > 0.88), and model fit criteria (SRMR = 0.069; NFI = 0.830). The results highlight the importance of competent and engaging lecturers in fostering positive attitudes toward learning statistics, while also emphasizing the need for adaptive and student-centered teaching strategies. This study contributes to the growing body of knowledge on educational quality and student engagement in quantitative disciplines, and offers practical implications for improving teaching practices in higher education, particularly in contexts where statistics is perceived as a challenging subject